1996
DOI: 10.1055/s-0038-1650635
|View full text |Cite
|
Sign up to set email alerts
|

Radiological Score in Paediatric Haemophilic Patients with Early and Late Onset of Factor VIII - Prophylaxis

Abstract: Dear Sir, Osteoathropathic alteration is a major cause of morbidity in patients with severe haemophilia. During infancy and adolescence, prophylaxis is undoubtedly preferable to on-demand therapy, but as yet poor data exist comparing the onset of prophylactic treatment at an early age with treatment initiated at a more advanced age (1,2,3). In order to determine which therapy regime is needed to prevent haemophilic arthropathy we prospectively compared 17 patients with moderate and severe haemophilia A (age: 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…Only in patients with adequate prophylaxis did joint scores remain at zero, or very low levels. In a recent German publication the authors concluded that prophylaxis is undoubtedly preferable to on-demand treatment during infancy and adolescence and not only patients with severe haemophilia but also those with moderate disease may benefit from early prophylaxis [8]. Our investigation, a 5-year review of the 34 youngest patients from the aforementioned series [2], yielded further evidence in favour of prophylactic treatment.…”
Section: Discussionmentioning
confidence: 51%
“…Only in patients with adequate prophylaxis did joint scores remain at zero, or very low levels. In a recent German publication the authors concluded that prophylaxis is undoubtedly preferable to on-demand treatment during infancy and adolescence and not only patients with severe haemophilia but also those with moderate disease may benefit from early prophylaxis [8]. Our investigation, a 5-year review of the 34 youngest patients from the aforementioned series [2], yielded further evidence in favour of prophylactic treatment.…”
Section: Discussionmentioning
confidence: 51%
“…Prophylactic replacement factor treatment, which has to start in early childhood, reduces the severity of spontaneous bleeding significantly [1,7,20] and can prevent or at least delay joint destruction [5]. The development of purified clotting factor concentrates, and the increased use of radiosynovectomy are two factors in current improvements in treatment leading to a significant reduction of the frequency of haemarthrosis [15].…”
Section: Discussionmentioning
confidence: 99%
“…It should also be emphasized that the introduction of new therapeutic approaches will change the economic analysis. For example, with the demonstration of the efficacy of long‐term prophylactic therapy of severe haemophilia [ 12–14], wider use of these costly regimens will increase the cost of treating noninhibitor patients [ 15, 16]. More detailed analyses should also include other direct and indirect health care costs of delivering health care to people with haemophilia, as factor concentrates comprise only the most obvious, albeit the greatest, of these costs [ 15].…”
Section: Discussionmentioning
confidence: 99%